KOMPENSASI SEBAGAI WUJUD PERLINDUNGAN HUKUM BAGI PEKERJA AKIBAT PEMUTUSAN HUBUNGAN KERJA SEPIHAK OLEH PENGUSAHA (STUDI KASUS: PUTUSAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR: 210/PDT.SUS-PHI/2019/PN.JKT.PST.) - Aufa Mubarok; Ariawan Ariawan (Jurnal Hukum Adigama, 2021)
Protection of workers who experience termination of employment unilaterally must receive proper protection in accordance with applicable laws. In contrast to unilateral layoffs carried out by companies to workers without clear reasons and without any discussion between employers and workers, which results in workers feeling disadvantaged because the termination of employment is not in accordance with Law No. 13 of 2003 concerning Manpower. From this problem that will be discussed is how the form of legal protection for workers who experience termination of employment unilaterally, to find out the company's responsibility for unilateral termination of employment, and to know the efforts made by workers who experience termination of employment unilaterally. The author uses normative legal research methods and uses interview data as supporting data. The results of the study reveal that workers who experience unilateral termination of employment can try to resolve disputes with the company through a bipartite process, if the bipartite process fails then it can be continued with the tripartite method through mediation. If there is no agreement between the worker and the entrepreneur, the dispute can be resolved through the industrial relations court.